2000
DOI: 10.1542/peds.106.4.e45
|View full text |Cite
|
Sign up to set email alerts
|

Time for a New Paradigm in Pediatric Medical Education: Teaching Neonatal Resuscitation in a Simulated Delivery Room Environment

Abstract: Realistic simulation-based training in neonatal resuscitation is possible using current technology, is well received by trainees, and offers benefits not inherent in traditional paradigms of medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
116
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(125 citation statements)
references
References 6 publications
0
116
0
6
Order By: Relevance
“…This is due in part to expert groups such as the Institute of Medicine and regulators like the Joint Commission for Accreditation of Health-care Organizations who advocate some type of team training. In addition, research suggests the need for improved teamwork and communication in neonatal intensive care, 2,3,16 emergency departments, 10 the operating room, 17,18 trauma resuscitation [19][20][21] and among residents of all disciplines. 22 Despite this interest and research, two recent reviews concluded that no studies have shown that team training can improve teamwork and the quality of care, 11,12 and a cluster randomized trial of team training for labor and delivery teams did not find significant changes in the process of care or outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…This is due in part to expert groups such as the Institute of Medicine and regulators like the Joint Commission for Accreditation of Health-care Organizations who advocate some type of team training. In addition, research suggests the need for improved teamwork and communication in neonatal intensive care, 2,3,16 emergency departments, 10 the operating room, 17,18 trauma resuscitation [19][20][21] and among residents of all disciplines. 22 Despite this interest and research, two recent reviews concluded that no studies have shown that team training can improve teamwork and the quality of care, 11,12 and a cluster randomized trial of team training for labor and delivery teams did not find significant changes in the process of care or outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with international programs, nurses can and should be trained for delivery-room care of the newborn, so that they can help the pediatrician or, in their absence, perform the initial procedures of neonatal resuscitation. 26,27 In Brazil, nurses can perform the initial steps of resuscitation and ventilation with bag and mask, in addition to helping pediatricians with chest compressions, intubation and drug administration. 28 Training of nursing students in the basic procedures of resuscitation, as recommended by the Brazilian Society of Pediatrics, 28 could contribute to reduce morbidity and mortality due to perinatal asphyxia in our country.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 In neonatology, simulations are used as training tools to improve team performance in neonatal resuscitation. 33,34 Louis Halamek was contacted by a member of Wee Deliver and after interview and discussion graciously agreed to be an expert resource and advisor for the group. The group's aim was improved team performance during high-risk delivery and newborn resuscitation.…”
Section: Methodsmentioning
confidence: 99%